EFFORTS TO STRENGTHEN MODERATE ISLAMIC THEOLOGICAL REASONING IN FACING THE ERA OF SOCIETY 5.0 - Mavianti Mavianti; Selamat Pohan; Othman Bin Hamzah (Proceeding International Seminar of Islamic Studies, 2023)
Adherents of Islam believe and make this belief a guide in living their lives. Even with this belief, you will feel peace and physicality which is manifested in social life. So that the behavior that appears is the impact of the practice of religion that he does. Islamic theological reasoning needs to be strengthened in facing the era of society 5.0 so that it can balance the social changes that are happening at this time. Because the strengthening of Islamic theological reasoning will become a stronghold for its adherents to be able to face an era full of technology like today. Moderate Islam is understood as teachings that are able to keep up with the times by not abandoning teachings that are in line with the guidance of the Al-Quran and Hadith. Thus, with an understanding related to Moderate Islam, it is hoped that Muhammadiyah cadres will be able to balance the movement of social change in life in society. Understanding of moderate Islamic values is currently beginning to be eroded by the changing times so that many young people tend to act pragmatically, exclusively and intolerantly in facing the era of society 5.0 where technology has its own portion for humans in living their lives